Ovine Pulmonary Adenocarcinoma - Iowa State University Center for Food Security and Public Health (Iowa State University Digital Repository, 2009)
Ovine pulmonary adenocarcinoma is a contagious viral disease of sheep that results in pulmonary neoplasia in some animals. The economic impact can be significant: up to 80% of the flock can be lost upon first exposure to the virus, with continuing losses that may be as high as 20% each year in some flocks. Excluding this disease from a flock is difficult, in part because no diagnostic test can detect animals in the preclinical stage. No effective treatment or vaccine is available, and eradication is challenging. Currently, ovine pulmonary adenomatosis exists in most sheep-raising areas of the world, with the exception of New Zealand and Australia. Iceland is the only country to have successfully eradicated this disease.